HUBUNGAN JUMLAH KUNJUNGAN ANC DAN STIGMATISASI DENGAN KEIKUTSERTAAN IBU HAMIL DALAM TES HIV SETELAH KONSELING OLEH PETUGAS KESEHATAN (Di Wilayah Kerja Puskesmas Turi Lamongan) - Ponco Indah Arista Sari; Agus Sulistyono; Hari Basuki Notobroto (The Indonesian Journal of Public Health, 2016)
HIV AIDS is considered as global threat due to the adverse impacts it brings to all sectors. The number of person with HIV-AIDS increases both in men and women. For pregnant women, HIV is not just a threat to the mother but also for the infant, therefore as to prevent the transmission and complication during pregnancy, screening should be made through an HIV test. The purpose of this study was to analyze the relationship between the number ofantenatal care and stigmatization on participation of pregnant women for HIV testing after counseling by Health Workers in the working area of Turi Public Health Center, Lamongan. This study applied cross sectional study. The population in this study consisted of 80 pregnant women. Simple random sampling was chosen for Sampling Technique and it was obtained as many as 42 respondents. Data collection was done using a questionnaire and interviews. Data were analyzed using frequency distribution tables and chi square test with significance level of 5% (p = 0.05). The results revealed that from as many as 42 pregnant women who made antenatal visit > 4 times, 100% of these pregnant women did not take HIV test while pregnant women who made only 2–4 times antenatal visit was as many as 16 individuals (64%) took the test, and only one pregnant woman who took the test on the first visit. Pregnant women who did not have the stigmatization, 100% took the HIV test. Statistical analysis showed no correlation between the number of antenatal visits (p = 0.000) and stigmastization (p = 0.000) of pregnant women for HIV testing after counseling by Health Workers. It is necessary to increase the provision of information and education for the pregnant women through health promotion concerning the importance of HIV testing and antenatal visits to the Health Care.Keywords: HIV test, Number of antenatal care, Stigmatization